The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1097/00006842-198407000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Growing Older with Cystic Fibrosis: Psychologic Adjustment of Patients More Than 16 Years Old

Abstract: The 79 female and 147 male patients constituting the population with cystic fibrosis (CF) aged 16 years and older attending The Hospital for Sick Children were asked to complete the Cornell Medical Index (CMI) and Tennessee Self-Concept Scale (TSCS); 64 female (81%) and 112 male (76%) subjects participated. Analysis of CMI results showed 43% of female subjects to have moderate to severe emotional disturbance compared to 19% of male subjects. This female : male ratio for severity of emotional disturbance is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…Vocational attainment is an important consideration and many individuals with CF are highly motivated to work with 94% indicating a current or past employment history. Studies surveying workforce participation rates range from 61% [16], 77% [17] to over 90% for combined work and advanced education participation [4,18]. The collective findings highlight that most CF patients have aspired to, or participated in, paid employment.…”
Section: Discussionmentioning
confidence: 90%
“…Vocational attainment is an important consideration and many individuals with CF are highly motivated to work with 94% indicating a current or past employment history. Studies surveying workforce participation rates range from 61% [16], 77% [17] to over 90% for combined work and advanced education participation [4,18]. The collective findings highlight that most CF patients have aspired to, or participated in, paid employment.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Cowen et al 9 found that 59% of women with CF over age 20 were emotionally distressed (as measured by the Cornell Medical Index), and 22% of adult men with CF were distressed.…”
Section: Introductionmentioning
confidence: 90%
“…Nineteen participants reported having, on average, 1.2 children living at home. The average number of years of education for subjects was 13.9 (SD, 2.7; range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The median age of the patients with CF was 26 years (range, 18-39); the median age of non-CF patients was 46 years (range, 18-62).…”
Section: Quality Of Life Indices For the Combined Sample Demographicsmentioning
confidence: 99%
“…di Sant' Agnese and Davis (1979) report that 85% of their adult cystic fibrosis patients were involved with school, career, or household chores. Similarly, Cowen et al (1984) report that 93% of the male and 85% of the female cystic fibrosis patients aged 16 or older either were attending school or were employed full-time.…”
mentioning
confidence: 98%